Investigation of the clinical performance of a novel solid‐state diagnostic dosimeter. (8th July 2015) - Tse, Jason; McLean, Donald
Abstract : This study investigated the clinical performance of a novel solid‐state diagnostic dosimeter, the RaySafe Xi transparent detector, by comparing its performance to a reference‐class ionization chamber. Firstly a comparison of dosimeter response "free‐in‐air" with standard beam qualities was made, followed by an investigation into its relative transparency in an X‐ray field and angular sensitivity dependence. The second part of the study looked at the overall performance of the transparent detector under scatter conditions with a number of beam qualities, including standard beam and those hardened by copper (Cu) filtration of thickness up to 0.9 mm, as would be encountered in the equipment testing of fluoroscopy systems. Overall, the transparent detector has demonstrated equivalent measurement properties to the ionization chamber under standard conditions and provided similar X‐ray attenuation as reflected by the nearly identical radiographic parameters selected for both dosimeters by the automatic dose rate control (ADRC) system. Yet, it also possessed an asymmetric angular response which respectively under‐ and overestimated the dose contribution from the rear and lateral directions by the same amount of 50%. The transparent detector provided comparable dose reading of ± 3 % to the ionization chamber with standard beam qualities and backscatter radiation present. These results were in good agreement with those of free‐in‐air measurement, indicating that the angular under‐ and overresponse might potentially compensate one another for accurate measurement. However, for identical Cu filtered beam qualities and setups, the transparent detector on average overresponded by 5.4% across the useful tube voltage range. In conclusion, the transparent detector, with its novel design, is essentially equivalent, within a 5% tolerance, to an ionization chamber, except in situations where beams hardened with Cu filtration are used with backscatter radiation present requiring larger uncertainty error estimations. PACS numbers: 87.57 uq, 87.59.C‐, 87.59.Dj